Promoting planetary health and well-being for all: harnessing indigenous knowledges for health with traditional, complementary and integrative health systems - Seifert, Georg; Boujnah, Hiba; Ghods, Roshanak; Wieland, Susan; Aginam, Obijiofor; Chuthaputti, Anchalee; Ghelman, Ricardo; Goh, Cheng Soon; Matsabisa, Motlalepula Gilbert; Tu'itahi, Sione; Kim, Sungchol; Kuruvilla, Shyama; et al. (Frontiers in Medicine, 2025)
The concept of well-being extends beyond individual health practices to encompass a burgeoning industry focusing on healthy lifestyles and products. This trend reflects a global paradigm shift toward prioritizing the holistic well-being of individuals and the planet within socioeconomic policies. This shift underscores the integration of social, economic, and environmental considerations into policy frameworks, signaling a concerted effort toward a more sustainable and health-conscious future. The article highlights the crucial role of Indigenous Knowledges for Health (IKH) and Traditional, Complementary and Integrative Health/Medicine (TCIH) systems in contributing to the interconnectedness between human well-being and the health of our planet through innovation, health promotion, and fair, equitable and sustainable benefit sharing. Various contemporary global problems stem from ways of thinking that prioritize the short-term economic interests of individuals or specific groups over the well-being of Peoples and the planet as a whole. In contrast, IKH and TCIH systems often inherently adopt a holistic, sustainable worldview where individual, community, and Planetary Health and well-being are intertwined, providing transformative solutions and models toward integrative health. By incorporating IKH and TCIH systems into contemporary development models, health, and medicine, we can promote health equity, improve well-being, and create a sustainable future for Peoples and the planet.